STUDENTS’ PROBLEMS AND STRATEGIES IN LEARNING SPEAKING SKILLS - Azizah, Geby; Dollah, Syarifuddin; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2023)
This study aims to find out what problems students face in learning speaking skills as researchers found several problems faced by students, one of which is the problem mentioned is a sense of insecurity because they feel uncomfortable when speaking English in front of many people, then the next problem is worried about making mistakes because they find it difficult to pronounce words in English, and also find it still difficult to string good and correct words in English and there are several strategies put forward by students to overcome the problem of difficulty speaking English in their environment, here are some of the strategies they provide to solve the problem of difficulty speaking English. Students said that they think teachers should provide vocabulary that is easy for students to memorize, and students also said that teachers should use English more often during English lessons so that students get used to it and teachers should use English more often during English lessons so that students get used to it. Other students also said that they have a special strategy, namely inviting their friends to learn English together so that they get used to the pronunciation, there is no embarrassment when they have to speak English in class and also said that during English learning, they should practice speaking more. While other students also have strategies that are almost the same as other students, namely students must memorize more vocabulary so that they are no longer afraid to arrange words in English. This research took place at SMA NEGERI 1 KAROSSA, Mamuju Tengah, Sulawesi Barat. The participants of this study were students of class X/1. The researcher used descriptive qualitative method with purposive sampling technique to select the participants. The instrument of this research was interview. Based on the results of interviews and observations, the researcher found that students have problems in learning speaking in class and not a few of them have strategies but are not conveyed and cannot apply them to overcome the problems they face. Furthermore, the researcher concluded that the application of strategies given by students can improve and help students to improve their speaking skills.